2017
DOI: 10.1002/anie.201705721
|View full text |Cite
|
Sign up to set email alerts
|

Human versus Robots in the Discovery and Crystallization of Gigantic Polyoxometalates

Abstract: The discovery of new gigantic molecules formed by self‐assembly and crystal growth is challenging as it combines two contingent events; first is the formation of a new molecule, and second its crystallization. Herein, we construct a workflow that can be followed manually or by a robot to probe the envelope of both events and employ it for a new polyoxometalate cluster, Na6[Mo120Ce6O366H12(H2O)78]⋅200 H2O (1) which has a trigonal‐ring type architecture (yield 4.3 % based on Mo). Its synthesis and crystallizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
114
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 114 publications
(122 citation statements)
references
References 30 publications
1
114
0
3
Order By: Relevance
“…The synthesis and crystallization of a polyoxometalate cluster were investigated via a ML classification algorithm. 25 The authors also reported the benefit of such a procedure in terms of accuracy and coverage of the crystallization space by comparing with human-based and random search approaches. Other examples integrating AI algorithms include the optimization of organic synthesis, [26][27][28] and the discovery of new multicomponent NiTi-based shape memory alloys.…”
Section: -9mentioning
confidence: 99%
“…The synthesis and crystallization of a polyoxometalate cluster were investigated via a ML classification algorithm. 25 The authors also reported the benefit of such a procedure in terms of accuracy and coverage of the crystallization space by comparing with human-based and random search approaches. Other examples integrating AI algorithms include the optimization of organic synthesis, [26][27][28] and the discovery of new multicomponent NiTi-based shape memory alloys.…”
Section: -9mentioning
confidence: 99%
“…Statistical methods were previously introduced to analyze the vast quantities of data generated by laboratory robots (6,7), and recently, machine learning algorithms have started to be integrated into laboratory equipment (8,9). However, most of these methods focus on the optimization of targeted properties (10,11) or require previous knowledge (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…It is evident by the increasing number of publications in which synthetic and computational chemistry, or materials development are mixed with machine learning (ML), robotics and artificial intelligence (AI), for example in Refs. [1][2][3][4][5][6]. DMT is promising less suitable models than possible.…”
Section: Introductionmentioning
confidence: 99%